Air annealing effect on scratch behaviour of BCN films. (July 2015) - Xu, S.; Ma, X.; Tang, G.; Zhang, Q.
<x content-type="archive" xml:space="preserve">Abstract</x> Boron carbon nitride BCN films have been deposited by direct current unbalanced magnetron sputtering. The obtained amorphous films are annealed in air atmosphere with different temperatures from 200 to 800C. The composition, microstructure, mechanical properties and scratch behaviour of BCN films were studied. The microstructures do not change significantly and mechanical properties decrease slightly when the annealing temperatures are below 400C. The films are oxidised and mechanical properties decline rapidly when annealing temperature rises to 600C. The scratch depth decrease and the highest critical load increases after the films are treated by air annealing below the oxidation temperature. The dominant deformation changes from elastic deformation to plastic deformation with the increase in annealing temperature. The coefficient of friction rise and surface smoothness decreases after BCN films are oxidised. BCN amorphous films have good interfacial adhesion before and after oxidation.